The Role of Leadership in The Sector Police in The Settlement Of Minor Crimes in The Legal Area of The Manyar Gresik Police. - Nugroho, Ady (Airlangga Development Journal, 2022)
The type of research used in this study is a qualitative descriptive type. The research location in this research is the Manyar Gresik Police. Data collection techniques were carried out by interview, observation and documentation. The results of the study indicate that the role of the Police Chief in resolving minor crimes in penal settlement is to carry out inherent supervision by monitoring, observing and checking the implementation of tasks so that they run according to plans and applicable regulations.